Developing Islamic-Nuanced Linear Algebra Module with Guided-Inquiry approach in the Matrix Material. (February 2019) - Mawardi, K; Dewi, E S; Asmah, S; Pratiwi, T N; Sari, U I; Putra, F G; Widayanti
Abstract: This research aims to develop and find out the feasibility of Islamic-Nuanced Linear Algebra Module with Guided-Inquiry approach in the Matrix Material. The research method is Research and Development (R & D) with the 4D model. The stages start with defining, designing, developing, dissemination. Validation was done by the material experts, Islamic experts, and media experts. Product testing was done through limited trials. Based on the results of the material expert validation, it obtained an average score of 3.6, Islamic experts obtained an average score of 4 and media experts obtained an average score of 3.7. Thus, the product is declared valid to be used after validating the results of the product and testing it to the student. Student responses were used to find out the feasibility of the product which obtained an average score of 3.4 with the highly attractive criteria.